2009
DOI: 10.1155/2009/293508
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis on the Effect of Radial Gap on Impeller‐Diffuser Flow Interaction as well as on the Flow Characteristics of a Centrifugal Fan

Abstract: The flow between the impeller exit and the diffuser entry (i.e., in the radial gap is generally considered to be complex). With the development of PIV and CFD tools such as moving mesh techniques, it is now possible to arrive at a prudent solution compatible with the physical nature of flow. In this work, numerical methodology involving moving mesh technique is used in predicting the real flow behavior, as exhibited when a target blade of the impeller is made to move past corresponding vane on the diffuser. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The selected 2D blade shape, circled in the solid black circle in Figure 12, has a near peak fitness value plotted in Figure 13 and the highest efficiency in Figure 12 among all GA designs. The fitness plot in Figure 13 is an inverse measurement of the defined objective function shown in (7). The final unconventional 2D design from the GA design iteration is shown in Figure 14.…”
Section: D Blade Profile Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected 2D blade shape, circled in the solid black circle in Figure 12, has a near peak fitness value plotted in Figure 13 and the highest efficiency in Figure 12 among all GA designs. The fitness plot in Figure 13 is an inverse measurement of the defined objective function shown in (7). The final unconventional 2D design from the GA design iteration is shown in Figure 14.…”
Section: D Blade Profile Optimizationmentioning
confidence: 99%
“…Lee and Bein [4] also applied steady CFD calculations to a centrifugal refrigerant compressor with an impeller, a vaneless diffuser, and a single discharge volute and obtained a good agreement in volute circumferential pressure with the measurements, particularly the pressure dip at the volute tongue. Meakhail and Park [5], Atif et al [6], and Karanth and Sharma [7] used both CFD and particle-image-velocity (PIV) measurement to study centrifugal fan impeller interactions with a vaned diffuser and a single discharge volute, and found that their steady numerical simulations were able to predict the flow characteristics, particularly the flow separation, which existed between the impeller and the diffuser. Although all three investigations [5][6][7] found that their prediction results agree with the measurements, Karanth and Sharma [7] revealed the presence of an optimum radial gap (or the interacting region) which could provide lower interaction losses.…”
Section: Introductionmentioning
confidence: 99%
“…PIV and CFD tools, such as meshing technique have provided a prudent solution which can assist in easy analysis of physical nature of flow. Karanth & Sharma [8], predicted the flow"s behavior due to the radial gap using numerical methodology and moving mesh technique. Presence of optimum radial gap provides lower loss coefficient, better energy conversion by impeller, and improved energy transformation by diffuser.…”
Section: Introductionmentioning
confidence: 99%
“…This makes accurately predicting fan performance using computational methods challenging. However, recent research has focused on elucidating the flow-field features associated with interaction between the impeller and diffuser [7], interaction between the impeller-scroll-inlet ring [8] and the clearance flow impact on overall fan performance [9,10]. The research objective has been to systematically characterise the flow-field in poorly conditioned regions of separated flow, and provide a basis for modelling the actual flow-field.…”
mentioning
confidence: 99%